Pityriasis rosea: Clinical profile from Central India - Namrata Chhabra; Neel Prabha; Sandeep Kulkarni; Satyaki Ganguly (Wolters Kluwer Medknow Publications, 2018)
Background: Pityriasis rosea (PR) is a common, self-limiting dermatologic disorder. The information regarding the clinical profile of the disease in India is limited because of inadequate studies. Materials and Methods: A retrospective, record-based study on the clinical presentation of PR was conducted in a tertiary care center based in Central India. Data of all the patients presenting to our outpatient department from October 2014 to March 2015 with a clinical diagnosis of PR were analyzed. Results: The age of the patients ranged from 9 to 54 (mean-20.32) years. There was a male preponderance with a male-to-female ratio of 1.3:1. History of prodromal symptoms was present in 11 (27.5%) patients. Pruritus was a common symptom in 30 of 40 (75%) patients. Of 40 patients, 15 (35%) had herald patch. The morphology of skin lesions was typical in most of the patients (77.5%). Two (5%) patients had papular skin lesions, four (10%) patients had erythema multiforme-like skin lesions, and one patient each had papulovesicular, psoriasiform, and eczematous skin lesions. Conclusion: The clinical features of most of the cases were mostly in accordance with the classical pattern of PR, with few unusual features.